2018
DOI: 10.1016/j.jhealeco.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Local neighbors as positives, regional neighbors as negatives: Competing channels in the relationship between others’ income, health, and happiness

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Such groups may either be defined in spatial terms (e.g. Luttmer, 2005;Kingdon and Knight, 2007;Ifcher et al, 2018), or in terms of similar demographic characteristics, particularly age and education (e.g. McBride, 2001;Ferrer-i Carbonell, 2005;Vendrik and Woltjer, 2007;Vendrik, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such groups may either be defined in spatial terms (e.g. Luttmer, 2005;Kingdon and Knight, 2007;Ifcher et al, 2018), or in terms of similar demographic characteristics, particularly age and education (e.g. McBride, 2001;Ferrer-i Carbonell, 2005;Vendrik and Woltjer, 2007;Vendrik, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empirical analyses of the relationship between others' income and SWB is divided into two lines of inquiry. 1 The bulk of this literature examines the relationship between measures of central tendency of a reference group's income distribution and SWB (see Ifcher et al (2016) for a review of the neighbors-income-SWB literature). A smaller literature considers the relationship between measures of dispersion and SWB, which is the focus of this paper (see Schneider (2015) for a review of the inequality-SWB literature).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, the neighbors-income-SWB literature has considered both large and small regions (e.g., ZIP codes). These multi-scale analyses have found that the neighbors-income-SWB relationship is scale-dependent: positive for small regions and negative for large regions (Brodeur & Fleche, 2016;Clark et al, 2009;Deaton & Stone, 2013;Ifcher et al, 2016;Kingdon & Knight, 2007). This literature suggests that the pattern emerges due to the relative magnitudes of mediators in the neighbors-income-SWB relationship; for example, public goods may dominate other mediators in small regions, while cost-of-living may dominate in large regions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Such groups may either be defined in spatial terms (e.g. Luttmer, 2005;Kingdon and Knight, 2007;Ifcher et al, 2018), or in terms of similar demographic characteristics, particularly age and education (e.g. McBride, 2001;Ferrer-i Carbonell, 2005;Vendrik and Woltjer, 2007;Vendrik, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%